Measuring Discoverability in Buildings Using Spatial Analysis and Occupant Surveys: A Study of the UWM Union - (:unkn) unknown (My University, 2020)
The architectural layout of a building influences the way people experience it. The more complex the layout, the overall size, the number of floors, and the more discrete spaces they contain, the harder it may be for people to discover the destinations and experiences that are available inside them. This is important because the more people are aware of what the building has to offer, the more likely they are to take advantage of these resources. This dissertation addresses the question: How do the layouts of buildings affect the potential of discoverability of places within them? This study introduces and develops the concept of discoverability as a critical imperative for the design of complex buildings. Discovery of spaces within buildings may be influenced by a variety of factors, including their location, visibility, the particular need the setting serves, word-of-mouth or hearing from others, and marketing efforts through signs, posters, or emails. Although each of these factors are important, this research focuses especially on the relationship between the visibility of a place and its discoverability. The study tries to develop a quantifiable definition for discoverability based on the measures derived from architectural analysis. The study evaluates three methods for measuring building configuration and visual accessibility: space syntax, visual graph analysis, and isovist analysis. Each approach offers benefits as well as shortcomings, the most important of which is their exclusive use of two-dimensional plan analysis. Thus, this study also introduces a new method for three-dimensional visual analysis using a Grasshopper script to produce a three-dimensional isovists. The result of the visibility analysis of the building was compared to the results from an online survey of students that assessed how they experience the Union and their familiarity with different areas inside this building. Results from the survey showed that the visibility of a place is the most important factor involved in its discovery. Comparing survey results with visibility analysis results also revealed that among the different methods, axial line analysis, derived through space syntax could best correlate with students’ responses about whether or not they discovered a place in the Union. The study also found that step depth, derived through visual graph analysis, is another important factor in the discoverability of places. The study provides an operational definition for discoverability based on these two concepts that can be used to measure how discoverable places are. The study also found that there was a relationship between the number of places that students had discovered in the Union and their perception of involvement opportunities in campus activities. This is an important finding which emphasized the importance of studying discoverability in complex settings like student union buildings.
Keywords: Discoverability; Isovist; Legibility; Space Syntax; Student Union; Visibility Analysis